Estimasi 3-d kedalaman batuan dasar menggunakan data geolistrik tahanan jenis konfigurasi dipole-dipole di Bukik Lantiak Padang Selatan - Hamidah Hamidah (Department of Physics – Universitas Negeri Padang UNP, 2016)
Bukik Lantiak which is located in Padang West Sumatera often has the landslide disaster. One of the factor that espouse landslide was the condition of the rock which was arrange the area such as bedrock. The type and the depth of bedrock in Bukik Lantiak was unknown. The research had done to know the type and the depth of bedrock. Resistivity Geoelectrical Dipole-dipole configuration was used as the method in this research. Interpreted of data had done with Smoothness-Counstraint Least-Square inversion. The research showed that the bedrock in the Bukik Lantiak is igneous rock, namely andesite. The bedrocks is found at a depth of more than 30 meters